Assessment of Some Engineering Geological Aspects of the Sub-soil of Ganakbari, Dhaka, Bangladesh - Haque, Md. Emdadul; Sayem, Hossain Md.; Kamal, Mostafa (Jahangirnagar University Environmental Bulletin, 2013)
The Madhupur Clay soil of the studied area is composed predominantly of silt size particles with small amount sand and clay. Three stratigraphic units have been identified namely unit A, unit B, and unit C. The lowermost unit (unit A) is mainly a sandy non cohesive unit. This unit is light reddish yellow or pale reddish yellow in colour, dense to very dense in nature. Unit B is mainly a silty sand unit which is mottled, light reddish yellow or pale reddish yellow in colour and medium dense to dense. The topmost unit (unit C) is mainly a clay unit which is pale grayish to light reddish yellow in colour, mainly medium to stiff in nature and show medium plasticity. The SPT value of study area ranges from 4 to 60 in the area and increases with increasing depth in all the bore holes. The layer of the cohesive clay soil (Unit C), extending to the depth of 0-28 feet, usually has the consistency that varies from medium to stiff. Further below, the non cohesive silty and sandy layers (Unit B & A respectively), extending to the depth of about 28-65 ft, usually have been found in a medium dense to very dense state. The sand percentages are increasing with increasing depth whereas the silt and clay percentages are decreasing with increasing depth. The obtained values of the Cu and Cg suggest that the studied samples are uniformly graded to well graded soil. The upper soil is suitable for light and moderate load bearing structures (up to 35 feet) whereas the lower soil is very much suitable for heavy structures (below 35 feet depth). Jahangirnagar University Environmental Bulletin, Vol.2, 61-70, 2013 DOI: http://dx.doi.org/10.3329/jueb.v2i0.16331